Catalisador sólido ácido obtido a partir do resíduo do caroço do açaí: estudo de sua atividade na reação de esterificação - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
Liquid inorganic acids are widely used as homogeneous catalysts in esterification reactions. Although highly active and low cost, it is imperative a tedious process for separation and purification of the final product. Besides the large volume of toxic and corrosive waste produced, there is also the drawback such as corrosion of equipment and difficulty for recycling the catalyst. Thereby, heterogeneous catalysis is a pathway to cleaner, safer and economically viable processes to produce chemicals for industry. Therefore, it is encouraged the production of heterogeneous catalysts must be at low cost and highly catalytic activity. Moreover, it is worldwide the use of biomass waste as raw materials for the production of heterogeneous catalysts. Herein, the acai stone (Euterpe oleracea Mart.), an amazon biomass waste from the processing of Acai fruits, was sulfonated and applied as a heterogeneous catalyst. By using esterification as model reaction we could check its catalytic active. The catalysts were synthesized at different carbonization temperatures, following the sulfonation by sulfuric acid at room temperature. The catalytic activity was tested in the reaction of oleic acid with methanol. For this reaction the experimental set was molar ratio of 1:12, 5% of catalyst, and reaction temperature of 100°C for 1h. The carbon material catalysts yielded 93% of methyl ester, while the reaction without catalyst showed 12% of methyl ester. In summary, this study shows promising results for obtaining carbon-based catalysts from the acai biomass waste and comes with the main novelty of preparing a sulfonic functionalized catalyst room temperature.
Keywords: Catálise heterogênea; Sulfonação; Resíduo da biomassa; Heterogeneous Catalysis; Sulfonation; Biomass waste; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA